Hypothermic treatment reduces matrix metalloproteinase-9 expression and damage in the liver following asphyxial cardiac arrest in rats - Donghwi Kim (Laboratory Animal Research, 2021)
Abstract Background Hypothermic treatment is known to protect organs against cardiac arrest (CA) and improves survival rate. However, few studies have evaluated the effects of hypothermia on CA-induced liver damages. This study was designed to analyzed the possible protective effects of hypothermia on the liver after asphyxial CA (ACA). Rats were randomly subjected to 5 min of ACA followed by return of spontaneous circulation (ROSC). Body temperature was controlled at 37 ± 0.5 °C (normothermia group) or 33 ± 0.5 °C (hypothermia group) for 4 h after ROSC. Liver tissues were extracted and examined at 6 h, 12 h, 1 day, and 2 days after ROSC. Results The expression of infiltrated neutrophil marker CD11b and matrix metallopeptidase-9 (MMP9) was investigated via immunohistochemistry. Morphological damage was assessed via hematoxylin and eosin (H & E) staining. Hypothermic treatment improved the survival rate at 6 h, 12 h, 1 day, and 2 days after ACA. Based on immunohistochemical analysis, the expression of CD11b and MMP9 was significantly increased from 6 h after ACA in the normothermia group. However, the expressions of CD11b and MMP9 was significantly decreased in the hypothermia group compared with that of the normothermia group. In addition, in the results of H & E, sinusoidal dilatation and vacuolization were apparent after ACA; however, these ACA-induced structural changes were reduced by the 4 h-long hypothermia. Conclusions In conclusion, hypothermic treatment for 4 h inhibited the increases in CD11b and MMP9 expression and reduced the morphological damages in the liver following ACA in rats. This study suggests that hypothermic treatment after ACA reduces liver damages by regulating the expression of CD11b and MMP9.